Attitudes towards work among prison inmates and the long-term unemployed - Parol, Robert (2015)
The article includes an analysis of differences in attitudes towards work in conditions of imprisonment and among employed and long-term unemployed men not detained in prison.The results of the analysis showed a moderate interaction effect of the factors: imprisonment and unemployment (F (1.407) = 6.16, p <0.05, Eta 2 = 0.36). It turned out that the environment of prison isolation and unemployment are mutually related, and the least favorable attitudes towards were shown by the men serving imprisonment sentence, having at the same time no employment opportunities.